The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1094/pdis-93-3-0224
|View full text |Cite
|
Sign up to set email alerts
|

Differential Responses of Resistant Soybean Entries to Isolates of Phakopsora pachyrhizi

Abstract: Soybean rust, caused by the fungus Phakopsora pachyrhizi, was detected in the continental United States in 2004. Several new sources of resistance to P. pachyrhizi have been identified in soybean (Glycine max); however, there is limited information about their resistance when challenged with additional U.S. and international isolates. Resistance of 20 soybean (G. max) entries was compared after inoculation with 10 P. pachyrhizi isolates, representing different geographic and temporal origins. Soybean entries i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
94
2
7

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(109 citation statements)
references
References 19 publications
6
94
2
7
Order By: Relevance
“…In contrast, the P. pachyrhizi isolates collected in Alabama in 2004 induced a susceptible reaction in Rpp1-carrying PI 200492. Pham et al (2009) confirmed that the rust isolates resulting in a susceptible reaction in PI 200492 already existed in Brazil by 2001. These findings suggest that initial entry of the pathogen was achieved by its long distance movement from Central or South America (Isard et al 2005, Pan et al 2006.…”
Section: Discussionsupporting
confidence: 57%
See 2 more Smart Citations
“…In contrast, the P. pachyrhizi isolates collected in Alabama in 2004 induced a susceptible reaction in Rpp1-carrying PI 200492. Pham et al (2009) confirmed that the rust isolates resulting in a susceptible reaction in PI 200492 already existed in Brazil by 2001. These findings suggest that initial entry of the pathogen was achieved by its long distance movement from Central or South America (Isard et al 2005, Pan et al 2006.…”
Section: Discussionsupporting
confidence: 57%
“…The US isolates expressing the same pathogenicity profile as US isolates collected in 2004 when soybean rust was first found in the US (Schneider et al 2005), have not been detected in subsequent US samples (Paul et al 2015, Paul & Hartman 2009, Pham et al 2009). Therefore, it has been suggested that P. pachyrhizi isolates existing in 2004 disappeared or were suppressed due to the subsequent winter, likely resulting in unfavorable conditions for pathogen survival a resistant reaction in response to 5%-53% of the rust populations.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…These resistance genes have been identified genetically but not yet cloned. Screening for resistance against P. pachyrhizi is generally done using three different infection phenotypes: the highest degree of protection was observed in the so-called "immune" response where no disease symptoms were found on soybean leaves upon inoculation with the pathogen (Bromfield, 1984;Pham et al, 2009). By contrast, susceptible interactions are characterized by tan-colored lesions, referred to as "TAN"-type, in which 2-5 uredia (syn.…”
Section: Breeding For Disease Resistance and Other Disease Managementmentioning
confidence: 99%
“…These genes are not effective against all populations of P. pachyrhizi [22]. The transfer of resistance genes through classical breeding or through marker-assisted selection allow to develop resistant varieties and their use as an efficient and costeffective method for soybean rust control.…”
Section: Introductionmentioning
confidence: 99%